2019
DOI: 10.1111/vop.12707
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous degeneration and associated ocular abnormalities in the dog

Abstract: Objective To identify the frequency of vitreous degeneration and its association with ocular comorbidities including cataracts, lens luxation, glaucoma, and retinal detachment. Methods This is a retrospective study of 4217 dogs from the Companion Animal Eye Registry (CAER) that underwent breed screening ophthalmic examinations between 2013 and 2016. The breeds analyzed included the Italian Greyhound, Shih Tzu, Affenpinscher, Bichon Frise, Brussels Griffon, Whippets, and Greyhound. Data collected from CAER incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 15 publications
6
9
3
1
Order By: Relevance
“…The former which was due to accumulation of calciumphospholipid complexes in the vitreous chamber could be seen as mobile with relation to the eye ball as observed by Labrueyre et al, (2007) andValetini et al, (2010). This was an age related vitreous degeneration as reported by Krishnan et al, (2020). Synchysis scintillans appeared like glistening structures with snow flurry appearance due to presence of cholesterol particles in liquefied vitreous as reported by Boeve and Stades (2007).…”
Section: Resultssupporting
confidence: 72%
“…The former which was due to accumulation of calciumphospholipid complexes in the vitreous chamber could be seen as mobile with relation to the eye ball as observed by Labrueyre et al, (2007) andValetini et al, (2010). This was an age related vitreous degeneration as reported by Krishnan et al, (2020). Synchysis scintillans appeared like glistening structures with snow flurry appearance due to presence of cholesterol particles in liquefied vitreous as reported by Boeve and Stades (2007).…”
Section: Resultssupporting
confidence: 72%
“…In addition, cataracts were more likely to occur in severe vitreous degeneration than in mild degeneration. The results of this study were similar to those of the study by Park et al, 9 which showed a positive correlation between cataract stages and severity of vitreous degeneration on ultrasonography, and were contrary to those of the study by Krishnan et al, 10 which revealed no association between vitreous degeneration and other ophthalmic diseases. It is presumed that the difference in results between our and Krishnan et al's study was due to the difference in samples.…”
Section: Discussionsupporting
confidence: 73%
“…To the best of our knowledge, no study has reported that vitreous degeneration causes nuclear cataracts. Moreover, two recent studies reported contradictory findings on the association between vitreous degeneration and cataracts 9,10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in humans, there are over 200 genes identified as causing retinal disorders. Progressive retinal atrophy and other ocular co-morbidities in Shih Tzu have been reported (Christmas 1992;Papaioannou & Dubielzig 2013;Krishnan et al 2020); however, the causative gene for PRA has not been identified in this dog breed.…”
Section: Introductionmentioning
confidence: 95%